Աղիքային դիսբակտերիոզի գնահատման մեթոդների համեմատություն - Անահիտ Մանվելյան; Մարինե Բալայան; Լենա Մալխասյան; Մարիաննա Իսաջանյան; Վարդան Ծատուրյան; Աստղիկ Փեփոյան (ՀՀ ԳԱԱ հրատ.)
Несмотря на развитие генетических методов идентификации микроорганизмов, микробиологический культуральный метод до сих пор широко применяется в медицинской и ветеринарной практике Республики Армения. Существуют опасения,что, помимо невозможности оценки некультивируемых видов микроорганизмов, применение культурального метода дает неоднозначные результаты и для культивируемых бактерий. Представленные исследования свидетельствуют о том, что культуральный анализ может с уверенностью применяться для идентификации бактерий родов Escherichia и Lactobacillus при оценке кишечного дисбактериоза. Despite the development of genetic methods for identification of microorganisms, microbiological cultural method is still widely used in medical and veterinary practice in the Republic of Armenia. There are concerns that, in addition to the incapability to assess the noncultivated microbial species, the use of the cultural method gives diverse results for cultivated bacteria too. The present study suggests that the cultural analysis can safely be used to identify the bacteria of the genera Lactobacillus and Escherichia when assessing intestinal dysbacteriosis.
Keywords: Science; Microbiology; Medicine